2005
DOI: 10.1136/jnnp.2003.034785
|View full text |Cite
|
Sign up to set email alerts
|

The spasticity paradox: movement disorder or disorder of resting limbs?

Abstract: Background: Spasticity is defined/assessed in resting limbs, where increased stretch reflex activity and mechanical joint resistance are evident. Treatment with antispastic agents assumes that these features contribute to the movement disorder, although it is unclear whether they persist during voluntary contraction. Objectives: To compare reflex amplitude and joint resistance in spastic and normal limbs over an equivalent range of background contraction. Methods: Thirteen normal and eight hemiparetic subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 37 publications
4
70
1
Order By: Relevance
“…The observed impaired modulation in firing rates during voluntary contractions is in contrast to the enhanced excitability of spastic-paretic motoneurons observed at rest (Mottram et al 2009(Mottram et al , 2010. These paradoxical findings are similar to previous observations for enhanced stretch or Hoffman reflexes at rest (Burne et al 2005;Chardon et al 2009;Huang et al 2006;Powers et al 1988), yet not during a background contraction (Burne et al 2005; Thompson et al 2009). We suggest that the enhanced reflex responses at rest in stroke survivors are explained by the presence of a low-level tonic depolarizing synaptic drive to the spastic-paretic motoneuron pool.…”
Section: Role Of Rate Saturation In Reduced Firing Rates Observed In supporting
confidence: 78%
“…The observed impaired modulation in firing rates during voluntary contractions is in contrast to the enhanced excitability of spastic-paretic motoneurons observed at rest (Mottram et al 2009(Mottram et al , 2010. These paradoxical findings are similar to previous observations for enhanced stretch or Hoffman reflexes at rest (Burne et al 2005;Chardon et al 2009;Huang et al 2006;Powers et al 1988), yet not during a background contraction (Burne et al 2005; Thompson et al 2009). We suggest that the enhanced reflex responses at rest in stroke survivors are explained by the presence of a low-level tonic depolarizing synaptic drive to the spastic-paretic motoneuron pool.…”
Section: Role Of Rate Saturation In Reduced Firing Rates Observed In supporting
confidence: 78%
“…increased muscle tone 50,69 . When background contractions are matched to normal levels in spastic subjects, little evidence exists for exaggerated reflex activity 58,61,70 (for exception see 71 ). However, during isotonic leg muscle contractions modulation and inhibition of Ib afferents (innervating the force sensitive Golgi tendon organs) is reduced 72 and some co-contraction of antagonistic arm muscles can occur 73,74 .…”
Section: Active Muscle In Non-functional Conditionsmentioning
confidence: 99%
“…The consequence is a reduced adaptation of muscle activity to the actual ground conditions 88 . Together with the reduced capacity to modulate reflex activity over the normal range, this might contribute to the spastic movement disorder 70,87 .…”
Section: Reflex Behaviourmentioning
confidence: 99%
“…Candidate mechanisms are the spinal reflex and passive muscle stiffness, both of which can potentially destabilize the joint. Both factors were found to be increased in UMND (Mirbagheri et al, 2001;Friden and Lieber, 2003;Lieber et al, 2004;Burne et al, 2005;de Vlugt et al, 2010). In a simulation study, the observed variation in clonus frequency with loading was explained from the isolated increased gain of the Ia reflex pathway (Hidler and Rymer, 2000).…”
Section: Introductionmentioning
confidence: 99%